The Food and Drug Administration-approved antipsychotic drug trifluoperazine, a calmodulin antagonist, inhibits viral replication through PERK-eIF2α axis - Mao, Yizhi; Wang, Ziyang; Yao, Chen; Zeng, Qi; Cheng, Wei; Zhang, Shimeng; Chen, Shuai; Sheng, Chunjie (Frontiers in Microbiology, 2022)
Virus-related diseases are seriously threatening human health, but there are currently only 10 viruses with clinically approved antiviral drugs available. As non-cellular organisms, viruses parasitize in living cells and rely on the protein synthesis mechanism of the host cells. In this study, we found that the antipsychotic drug trifluoperazine (TFP), a dual dopamine receptor D2 (DRD2) / calmodulin (CALM) antagonist, increases the phosphorylation of eukaryotic initiation factor 2α (eIF2α), a key factor in the regulation of protein synthesis and significantly inhibits VSV and HSV-1 replication. CALM but not DRD2 is involved in the antiviral activity of TFP. By knockdown of protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) we found that the antiviral function of TFP is dependent on PERK, a stress response kinase that mediates eIF2α phosphorylation. Furthermore, the results of animal experiments showed that TFP protects mice from lethal VSV attacks, improving the survival rate and reducing lung injury. Taken together, these data suggests that TFP inhibits virus replication through PERK-eIF2α axis, and this broad-spectrum of mechanisms are worth further evaluation in clinical trials in the future.